Creation of an innovative health and rehabilitation center - Балджи, Марина Дмитрівна; Baldzhy, M. D. (My University, 2023)
The paper considers the need to create an innovative health and rehabilitation center due to the long-term military aggression of russia. The latter leads to the fact that many military and civilians receive physical and psychological injuries that need to be treated. At the first stage of rehabilitation, these problems are solved by special medical facilities, while the restoration of both physical and psychological condition should be carried out outside hospitals. One of these facilities could be health and rehabilitation centers on a national scale. Such centers can be formed on the basis of existing sports complexes, where there is a basis for carrying out appropriate actions. The article uses the example of the Olimp sports complex located on the Black Sea coast to illustrate the prospects of this area. The relevance of the work is due to the needs of the present and the principles of sustainable development of society, which combines social (human factor), economic (economic factor) and environmental (health improvement through a clean environment) components. The purpose of the study is to substantiate the creation of an innovative health and rehabilitation center on the basis of the Olimp sports complex for military and civilians suffering from physical and psychological injuries. Research methods: analysis and evaluation of economic activities; methods of generalization for the study of activities; observation method for the study of economic activities of FSC Olimp and the peculiarities of its services. The results of the work include: research on the needs of creating a health and rehabilitation center; identification of the main forms and types of work of the health and rehabilitation center; analysis of the activity of the physical culture and sports complex "Olympus"; assessment of the importance of introducing health and rehabilitation services; development of ways of innovative health and rehabilitation activities. The scientific novelty lies in the development of innovative approaches for the creation of a health and rehabilitation center that can operate on the basis of the Olimp sports complex. Practical significance of the results. The system for creating an innovative health and rehabilitation center is proposed for a specific existing enterprise and can be implemented in the near future. The developed recommendations can be used for a similar type of enterprise.

У роботі розглядаються потреби створення інноваційного оздоровчо- реабілітаційного центру, обумовлені багаторічною військовою російською агресією. Остання призведе до того, що багато військових і цивільних отримують фізичні та психологічні травми, які потрібно лікувати. Ці проблеми на першому етапі оздоровлення вирішують спеціальні лікарські заклади, а відновлення як фізичного, так і психологічного стану має здійснюватись поза межами лікарень. Одними з таких об’єктів можуть стати, в масштабах країни, оздоровчо- реабілітаційні центри. Формування таких центрів може відбуватись на базі існуючих спортивних комплексів, де є підґрунтя для проведення відповідних дій. На прикладі роботи фізкультурно-спортивного комплексу «Олімп», розташованого на узбережжі Чорного моря, розглядається перспективна діяльність даного напрямку. Актуальність роботи обумовлена потребами сьогодення і принципами сталого розвитку суспільства, в якому поєднуються соціальна (людський фактор), економічна (господарський фактор) та екологічна (оздоровлення завдяки чистому довкіллю) складові. Мета полягає в обґрунтуванні створення інноваційного оздоровчо-реабілітаційного центру на базі фізкультурно-спортивного комплексу «ОЛІМП» для військових і цивільних, які отримують фізичні та психологічні травми. Методи дослідження: аналіз та оцінка господарської діяльності; методи узагальнення для дослідження діяльності; метод спостереження для дослідження господарської діяльності ФСК «Олімп» та особливостей надання ним послуг. Результати роботи включають: дослідження потреб створення оздоровчо- реабілітаційного центру; виявлення основних форм і видів роботи оздоровчо-реабілітаційного центру; аналіз діяльності фізкультурно-спортивного комплексу «Олімп»; оцінка вагомості запровадження оздоровчо-реабілітаційних послуг; розробка шляхів інноваційної оздоровчо- реабілітаційної діяльності. Наукова новизна полягає у розробці інноваційних підходів для створення оздоровчо- реабілітаційного центру, який може працювати на базі фізкультурно-спортивного комплексу «Олімп». Практичне значення отриманих результатів. Система створення інноваційного оздоровчо- реабілітаційного центру запропонована для конкретного існуючого підприємства і може бути реалізована у найближчий час. Розроблені рекомендації можуть бути використані для аналогічного типу підприємств.
Baldzhy M. D. Creation of an innovative health and rehabilitation center / M. D. Baldzhy // Актуальні проблеми розвитку економіки регіону. - 2023. - Вип 19. - Т. 2. - 235-243. doi: 10.15330/apred.2.19.235-243
Keywords: health and rehabilitation center; physical culture and sports complex; implementation of services; system of discounts; price incentives; оздоровчо-реабілітаційний центр; фізкультурно-спортивний комплекс; реалізація послуг; система знижок; цінове стимулювання; Research Subject Categories::SOCIAL SCIENCES